2016
DOI: 10.15517/rbt.v64i3.19537
|View full text |Cite
|
Sign up to set email alerts
|

Concentraciones de alcaloides, glucósidos cianogénicos, polifenoles y saponinas en plantas medicinales seleccionadas en Ecuador y su relación con la toxicidad aguda contra Artemia salina

Abstract: Concentraciones de alcaloides, glucósidos cianogénicos, polifenolesy saponinas en plantas medicinales seleccionadas en Ecuador y su relación con la toxicidad aguda contra Artemia salina Alcoholic and aqueous extracts from leaves of these selected plants were prepared at different concentrations. To assess cytotoxicity of these extracts, different bioassays with A. salina were undertaken, and the mortality rates and LC 50 were obtained. Besides, concentrations of alkaloids, cyanogenic glycosides, phenols, tanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 40 publications
1
4
0
4
Order By: Relevance
“…Root extract of Taraxacum officinale revealed the presence of cardiac glycosides, terpenoids (antiviral activity), phenols (Immuno modulatory and antihyperglycemic) (Kenny et al, 2015) , tannins (wound healing activity) (Ajaz et al, 2019), flavonoids (antioxidant and antiinflammatory activity) (Hagymási et al, 2000), steroids and sterols (Antihyperglycemic and Anti inflammatory activity) (Petlevski et al, 2003) (Jones and Persaud, 1998) carbohydrates, proteins and amino acids with absence of alkaloids and fixed oil. Also similar finding reported in the other species of the same family (Jaramillo-Jaramillo et al, 2016). HPTLC is one of the most demanding technical methods for the quantitative and qualitative analysis of medicinal plants (Marston, 2007).…”
Section: Resultssupporting
confidence: 83%
“…Root extract of Taraxacum officinale revealed the presence of cardiac glycosides, terpenoids (antiviral activity), phenols (Immuno modulatory and antihyperglycemic) (Kenny et al, 2015) , tannins (wound healing activity) (Ajaz et al, 2019), flavonoids (antioxidant and antiinflammatory activity) (Hagymási et al, 2000), steroids and sterols (Antihyperglycemic and Anti inflammatory activity) (Petlevski et al, 2003) (Jones and Persaud, 1998) carbohydrates, proteins and amino acids with absence of alkaloids and fixed oil. Also similar finding reported in the other species of the same family (Jaramillo-Jaramillo et al, 2016). HPTLC is one of the most demanding technical methods for the quantitative and qualitative analysis of medicinal plants (Marston, 2007).…”
Section: Resultssupporting
confidence: 83%
“…Among these molecules, (Z)‐Ascaridole which is another monoterpen, was the most active compound and thus has shown the strongest fumigant activity against S. zeamais. According to, [17] Colombian D. ambrosioides leaves was obtained using hydrodistillation, and its volatile chemical composition was determined by gas chromatography coupled with a mass spectrometry detector (GC‐MS), showing the presence of the following molecules: Estragol, Eugenol, (E)‐Carveol and Carene (belonging to the carene family) which was among the predominant compounds in the essential oil [18] . reported that the essential oil from Indian D. ambrosioides leaves was analyzed using a gas chromatography coupled with mass spectrometry detector (GC‐MS), and allowed the identification of the following compounds : Benzaldehyde, Dihydrocarvyl acetate and Pinocarvone which was present as a minority compound.…”
Section: Resultsmentioning
confidence: 99%
“…El conocimiento de los principios bioactivos que poseen las personas sobre las plantas existentes en los ecosistemas de la zona sur de Manabí servirá de punto de partida para futuras investigaciones en la rama de la bioquímica. Este hecho, según Beyra et al (2004); Ugartemendia-Ugalde et al (2015), a su vez contrasta con el creciente interés del mundo académico por conocer los principios bioactivos de las especies consideradas como medicinales; esos autores desarrollaron investigación bibliográfica partiendo de las plantas catalogadas como medicinales, como por ejemplo, especies de los géneros: Mentha, Matricaria, Valeriana, Passiflora, Citrus, entre otros; por otra parte, Jaramillo-Jaramillo et al (2016) plantearon que el contenido de metabolitos secundarios hallados en plantas les atribuye un gran valor farmacológico.…”
Section: Discussionunclassified